DEVELOPMENT AND IN VIVO EVALUATION LOVASTATIN BY SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the present investigation, self-nanoemulsifying drug delivery system (SNEDDS), of Lovastatin is being formulated to increase the solubility and bioavailability. The optimized Lovastatin SNEDDS formulation (F8) has a composition of Acrysol EL 135 as oil phase, Lauro glycol 90 and Capmul MCM as surfactant and co-surfactant respectively. Formulation F8 was found to be best formulation based on evaluation parameters. No drug precipitation or phase separation was observed in the optimized formulation. The particle size of the optimized formulation was found to be 4.9 nm & Z-Average of 71.5 nm indicating all the particles were in the nanometer range. The zeta potential of the optimized SNEDDS formulation was found to be -13.7 mV which comply with the requirement of the zeta potential for stability. Furthermore, pharmacokinetic studies in rats indicated that compared to the pure drug, the optimized SMEDDS formulation significantly improved the oral bioavailability of Lovastatin. Therefore, from our results the study suggests that the Lovastatin loaded self-nanoemulsifying formulation has a great potential for clinical application.